Development of Indian Runner Ducks: Indonesia's Original Germplasm Superior Laying Duck - Budi Indarsih; Mohammad Hasil Tamzil; Syamsuhaidi Syamsuhaidi (Universitas Sebelas Maret, 2024)
Objective: This review article aims to provide a comprehensive overview of the origins of the Indian Runner duck and its development as a significant source of egg production in Indonesia. It reviews recent scientific literature on the topic, synthesizing findings from various studies.Methods: Analysis of the data reveals that the Indian Runner duck descends from the wild green-headed Mallard, which was domesticated in both mainland China and Indonesia.Results: The qualitative and quantitative traits of Indian Runner ducks are exceptionally high, making them suitable for various selection purposes. Specifically, selection processes have been implemented for egg production in Mojosari ducks, leading to the development of Mojomaster-Agrinak ducks, as well as in Alabio ducks, resulting in Alabimaster-Agrinak ducks. The crossbreeding of Mojomaster-Agrinak ducks as the male line with Alabimaster-Agrinak ducks as the female line yields superior hybrid offspring known for their auto-sexing characteristics.Conclusion: Ultimately, Mojomaster and Alabimaster ducks are recognized as superior laying duck varieties, with their interbreeding producing commercial laying ducks that exhibit auto-sexing traits at the day-old (DOD) stage.